Environment and investment agreements: Together, apart? - Ralph Janik (FIW - Research Centre International Economics, 2024)
The global investment regime stands at a crossroads. From the late 1980s onwards, its predominant, if not exclusive focus on economic growth has been increasingly shifting towards sustainable development. The delicate balance between these considerations is reflected in bilateral or multilateral negotiations , national legislation, and decisions by domestic courts or investment tribunals. One does not work without the other. To contribute to this discussion, this policy brief summarizes existing environmental provisions in investment treaties and and free trade agreements to outline their potential role as part of the 2030 Agenda for Sustainable Development. In so doing, it summarizes the positions of the relevant multilateral institutions and fora, namely the UN Conference on Trade and Development, the OECD, or the United Nations Commission on International Trade Law. The general assumption is clear: While investment protection in general and investor-state-dispute settlement is under enormous pressure due to accusations of ignoring societal values such as environmental concerns, calls for disbanding it are premature. Foreign direct investment can and should play More, not less, foreign direct investment is needed to protect the environment.
Keywords: 330